To remove the buckle or watch? - Kunal K Shah; Ekta Rishi; Pramod Bhende; Pukhraj Rishi; Tarun Sharma (Indian Journal of Ophthalmology, 2019)
Scleral buckling is one of the most effective modality for treatment of rhegmatogenous retinal detachment and in selected cases of retinopathy of prematurity. Although quite safe, it has its own set of associated morbidities. This report presents an interesting case, where the scleral buckle migrated posteriorly reaching up to the optic nerve.